INTRODUCING PRAGMATICS IN USE (2ND EDITION) - Loc, Le Huu (VNU Journal of Foreign Studies; Vol 38 No 6, 2022)
Among the array of textbooks on linguistics in general and of pragmatics in particular, Introducing Pragmatics in Use (2nd edition) has emerged as a user-friendly guide to the field of pragmatics as it has been described as “a lively and accessible introduction to pragmatics” (O’Keeffe, Clancy & Adolphs, 2020). As its name suggests, the book is designed with the combination of theoretical and practical aspects of pragmatics by not only introducing theories but also guiding the employment of the theories to examine real or naturally-occurring data in spoken and written forms. Introducing Pragmatics in Use (2nd edition) makes systematic use of several language corpora and related software programs. The adoption of the corpus technique to investigate key component areas, namely reference, speech acts, linguistic politeness, language variety, and register is its central focus. By analyzing various language settings offered by spoken and written corpora, the book aims at contextualizing pragmatics in linguistic study as well as making suggestions concerning applying pragmatics to teaching languages. It seeks to provide an introduction to the key theoretical and methodological issues in the study of Pragmatics; therefore, it is a good choice for senior undergraduate or graduate students enrolled in the courses of TESOL, applied linguistics, discourse analysis, corpus linguistics, or research methods in applied linguistics so that they can enhance their understanding of corpus pragmatics and apply its methodology to serve their researching and teaching purposes.